Keterlibatan Konsumen Dalam Kebaruan Produk - Ignasius Heri Satrya Wangsa; Lina Lina (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2022)
Involvement is a key word in the context of product novelty, when businesses are required to become more competitive in product innovation. This point of view forms the basis for understanding the two concepts of business existence. First, the demand to develop new products is directed to product innovation because technology is increasingly developing. Novelty needs to keep pace with technological advances as well as be market-oriented. Second, the business builds a collaborative commitment with its customers. This indicates a position where the relationship with the market demands an equal role. Businesses no longer take distance in building relationships with their markets. Thus consumers will gothrough a dynamic process in the experience of using the product, and businesses will continue to consistently motivate consumer learning in the process of product novelty adoption. This study aims to explain consumer’s learning experience on product novelty from the process of consumer involvement in the holistic experience of responding to product novelty. A combined quantitative-qualitative approach (mixed-method approach) is applied. The quantitative approach was carried out using SEM analysis with the SmartPLS tool on 113 respondents, while the qualitative approach was carried out using the Interpretative Phenomenological Analysis (IPA) technique on participant narratives. Furthermore, from the two approaches, an integration process was carried out to find the grand theme of consumer learning experiences in the context of their involvement in responding to product novelty. Through this research, it can be seen that the product novelty learning experience is formed through initial involvement to recognize, andcontinued involvement in using the product. The product novelty learning experience is the involvement of consumers in realizing essential realities, practical realities, and contextual realities.